Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the given system of equations, we have:
[tex]\[ \begin{aligned} 1: & \quad 2x + 4y - 3z = 12 \\ 2: & \quad -3x - 2y + 2z = -9 \\ 3: & \quad -x + y - 3z = 0 \end{aligned} \][/tex]
We need to find values for [tex]\( x \)[/tex], [tex]\( y \)[/tex], and [tex]\( z \)[/tex] that satisfy all three equations. Let's proceed step-by-step.
### Step 1: Solve for One Variable
Begin with equation [tex]\(3\)[/tex]:
[tex]\[ -x + y - 3z = 0 \][/tex]
Rearrange to solve for one variable, say [tex]\( y \)[/tex]:
[tex]\[ y = x + 3z \quad \text{(Equation 3')} \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into Equations 1 and 2
Substitute [tex]\( y = x + 3z \)[/tex] into equations 1 and 2:
#### For Equation 1:
[tex]\[ \begin{aligned} 2x + 4y - 3z &= 12 \\ 2x + 4(x + 3z) - 3z &= 12 \\ 2x + 4x + 12z - 3z &= 12 \\ 6x + 9z &= 12 \\ \end{aligned} \][/tex]
Simplify:
[tex]\[ 6x + 9z = 12 \quad \text{(Equation 1')} \][/tex]
Divide the entire equation by 3:
[tex]\[ 2x + 3z = 4 \quad \text{(Equation 1'')} \][/tex]
#### For Equation 2:
[tex]\[ \begin{aligned} -3x - 2y + 2z &= -9 \\ -3x - 2(x + 3z) + 2z &= -9 \\ -3x - 2x - 6z + 2z &= -9 \\ -5x - 4z &= -9 \\ \end{aligned} \][/tex]
Simplify:
[tex]\[ -5x - 4z = -9 \quad \text{(Equation 2')} \][/tex]
### Step 3: Solve the Simplified System of Two Variables
Now we have a simpler system of two equations with two variables:
[tex]\[ \begin{aligned} 1'': & \quad 2x + 3z = 4 \\ 2': & \quad -5x - 4z = -9 \end{aligned} \][/tex]
Let's solve these equations simultaneously.
#### Solve Equation 1'' for [tex]\( x \)[/tex]:
[tex]\[ 2x + 3z = 4 \\ 2x = 4 - 3z \\ x = \frac{4 - 3z}{2} \quad \text{(Equation 4)} \][/tex]
#### Substitute Equation 4 into Equation 2':
[tex]\[ -5 \left( \frac{4 - 3z}{2} \right) - 4z = -9 \\ - \frac{20 - 15z}{2} - 4z = -9 \\ -10 + \frac{15z}{2} - 4z = -9 \\ -10 + \frac{15z}{2} - \frac{8z}{2} = -9 \\ -10 + \frac{7z}{2} = -9 \\ \frac{7z}{2} = 1 \\ 7z = 2 \\ z = \frac{2}{7} \][/tex]
### Step 4: Substitute [tex]\( z \)[/tex] into Equation 4 to Find [tex]\( x \)[/tex]:
[tex]\[ x = \frac{4 - 3z}{2} \\ x = \frac{4 - 3 \left( \frac{2}{7} \right)}{2} \\ x = \frac{4 - \frac{6}{7}}{2} \\ x = \frac{\frac{28}{7} - \frac{6}{7}}{2} \\ x = \frac{\frac{22}{7}}{2} \\ x = \frac{22}{14} \\ x = \frac{11}{7} \][/tex]
### Step 5: Substitute [tex]\( x \)[/tex] and [tex]\( z \)[/tex] into Equation 3' to Find [tex]\( y \)[/tex]:
[tex]\[ y = x + 3z \\ y = \frac{11}{7} + 3 \left( \frac{2}{7} \right) \\ y = \frac{11}{7} + \frac{6}{7} \\ y = \frac{17}{7} \][/tex]
### Final Solution:
The solutions to the system of equations are:
[tex]\[ x = \frac{11}{7}, \quad y = \frac{17}{7}, \quad z = \frac{2}{7} \][/tex]
These values satisfy all the given equations.
[tex]\[ \begin{aligned} 1: & \quad 2x + 4y - 3z = 12 \\ 2: & \quad -3x - 2y + 2z = -9 \\ 3: & \quad -x + y - 3z = 0 \end{aligned} \][/tex]
We need to find values for [tex]\( x \)[/tex], [tex]\( y \)[/tex], and [tex]\( z \)[/tex] that satisfy all three equations. Let's proceed step-by-step.
### Step 1: Solve for One Variable
Begin with equation [tex]\(3\)[/tex]:
[tex]\[ -x + y - 3z = 0 \][/tex]
Rearrange to solve for one variable, say [tex]\( y \)[/tex]:
[tex]\[ y = x + 3z \quad \text{(Equation 3')} \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into Equations 1 and 2
Substitute [tex]\( y = x + 3z \)[/tex] into equations 1 and 2:
#### For Equation 1:
[tex]\[ \begin{aligned} 2x + 4y - 3z &= 12 \\ 2x + 4(x + 3z) - 3z &= 12 \\ 2x + 4x + 12z - 3z &= 12 \\ 6x + 9z &= 12 \\ \end{aligned} \][/tex]
Simplify:
[tex]\[ 6x + 9z = 12 \quad \text{(Equation 1')} \][/tex]
Divide the entire equation by 3:
[tex]\[ 2x + 3z = 4 \quad \text{(Equation 1'')} \][/tex]
#### For Equation 2:
[tex]\[ \begin{aligned} -3x - 2y + 2z &= -9 \\ -3x - 2(x + 3z) + 2z &= -9 \\ -3x - 2x - 6z + 2z &= -9 \\ -5x - 4z &= -9 \\ \end{aligned} \][/tex]
Simplify:
[tex]\[ -5x - 4z = -9 \quad \text{(Equation 2')} \][/tex]
### Step 3: Solve the Simplified System of Two Variables
Now we have a simpler system of two equations with two variables:
[tex]\[ \begin{aligned} 1'': & \quad 2x + 3z = 4 \\ 2': & \quad -5x - 4z = -9 \end{aligned} \][/tex]
Let's solve these equations simultaneously.
#### Solve Equation 1'' for [tex]\( x \)[/tex]:
[tex]\[ 2x + 3z = 4 \\ 2x = 4 - 3z \\ x = \frac{4 - 3z}{2} \quad \text{(Equation 4)} \][/tex]
#### Substitute Equation 4 into Equation 2':
[tex]\[ -5 \left( \frac{4 - 3z}{2} \right) - 4z = -9 \\ - \frac{20 - 15z}{2} - 4z = -9 \\ -10 + \frac{15z}{2} - 4z = -9 \\ -10 + \frac{15z}{2} - \frac{8z}{2} = -9 \\ -10 + \frac{7z}{2} = -9 \\ \frac{7z}{2} = 1 \\ 7z = 2 \\ z = \frac{2}{7} \][/tex]
### Step 4: Substitute [tex]\( z \)[/tex] into Equation 4 to Find [tex]\( x \)[/tex]:
[tex]\[ x = \frac{4 - 3z}{2} \\ x = \frac{4 - 3 \left( \frac{2}{7} \right)}{2} \\ x = \frac{4 - \frac{6}{7}}{2} \\ x = \frac{\frac{28}{7} - \frac{6}{7}}{2} \\ x = \frac{\frac{22}{7}}{2} \\ x = \frac{22}{14} \\ x = \frac{11}{7} \][/tex]
### Step 5: Substitute [tex]\( x \)[/tex] and [tex]\( z \)[/tex] into Equation 3' to Find [tex]\( y \)[/tex]:
[tex]\[ y = x + 3z \\ y = \frac{11}{7} + 3 \left( \frac{2}{7} \right) \\ y = \frac{11}{7} + \frac{6}{7} \\ y = \frac{17}{7} \][/tex]
### Final Solution:
The solutions to the system of equations are:
[tex]\[ x = \frac{11}{7}, \quad y = \frac{17}{7}, \quad z = \frac{2}{7} \][/tex]
These values satisfy all the given equations.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.